УЧАСТЬ УКРАЇНИ В УНІВЕРСАЛЬНІЙ МІЖНАРОДНО-ПРАВОВІЙ СИСТЕМІ ПРОТИДІЇ ДИСКРИМІНАЦІЇ ОСІБ З ВІЛ-ПОЗИТИВНИМ СТАТУСОМ У ТРУДОВИХ ВІДНОСИНАХ - Ануфрієв, Микола Іванович; Шашкова-Журавель, Ірина Олександрівна (SUPREMANCE OF LAW, 2018)
This article is devoted to the comprehensive study of Ukraine’s participation in the universal international legal system for combating discrimination against people living with HIV and AIDS in labor relations. The main attention is paid to the analysis of international legal acts of the United Nations and the International Labor Organization concerning the protection of labor rights of HIV-positive persons from the point of view of their requirements at the level of Ukrainian legislation. Also, the article covers the fundamental norms of the laws of Ukraine and state programs aimed at protecting people living with HIV from discrimination in the workplace. Thus, the authors draw attention to the lack of a clear definition at the level of the fundamental anti-discriminatory international legal acts of the United Nations and the International Labor Organization of the HIV-positive status of a person as a sign of prohibited discrimination, including in the field of labor. At the same time, the article shows the development of the international legal system for combating discrimination against HIV-infected persons, including in the field of labor, which, in particular, is reflected in the adoption of General Constitutional Observations, supplemented by the provisions of the fundamental human rights international legal acts of the United Nations in connection with the need for their interpretation to protect the rights of HIV-infected people and people with AIDS. The article provides an analysis of the provisions of the declarations of the United Nations and UNESCO that provide an international foundation for tolerant attitude towards HIV-infected workers and ensure their equality in labor relations. The authors pay particular attention to the study of the practical rules and guidelines that were adopted within the framework of the International Labor Organization, which are directly aimed at protecting labor rights and combating discrimination and stigmatization of people living with HIV and AIDS in the workplace. The article analyzes the provisions of the laws of Ukraine, the goals of state programs, as well as the norms of bills on the protection of HIV-positive persons from discrimination in labor relations. The authors state that, despite the optional nature of most of the universal international legal norms aimed at protecting the work of HIV-infected and AIDS patients, their provisions were mostly taken into account by the legislator of Ukraine. The authors also provide a vision of ways to increase the effectiveness of implementation at the national level of the requirements of universal international legal norms on the protection of labor rights of people living with HIV / AIDS.